2022
DOI: 10.3390/ijms23073984
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Effects of Auto-Antibodies on Angiotensin II Type 1 Receptor Signaling and Cell Proliferation

Abstract: The angiotensin II (Ang II) type 1 receptor (AT1R) is involved in the regulation of blood pressure (through vasoconstriction) and water and ion homeostasis (mediated by interaction with the endogenous agonist). AT1R can also be activated by auto-antibodies (AT1R-Abs), which are associated with manifold diseases, such as obliterative vasculopathy, preeclampsia and systemic sclerosis. Knowledge of the molecular mechanisms related to AT1R-Abs binding and associated signaling cascade (dys-)regulation remains fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…A limitation of our study is that only one MoAb has been tested. It may be that the antibody will be more effective at higher antibody concentrations, as in some papers even concentrations up to 1 mg/ml are used, 22 but we question whether such antibody concentrations are clinically relevant as we found that anti‐RhoGDI2 antibody concentrations in patients are around 10 μg/ml. Patient sera containing high anti‐RhoGDI2 antibody titers added to starved endothelial cells seem to activate complement, but the usage of patient sera exhibit some drawbacks such as effects of serum components other than anti‐RhoGDI2 antibodies on complement activation.…”
Section: Discussionmentioning
confidence: 79%
“…A limitation of our study is that only one MoAb has been tested. It may be that the antibody will be more effective at higher antibody concentrations, as in some papers even concentrations up to 1 mg/ml are used, 22 but we question whether such antibody concentrations are clinically relevant as we found that anti‐RhoGDI2 antibody concentrations in patients are around 10 μg/ml. Patient sera containing high anti‐RhoGDI2 antibody titers added to starved endothelial cells seem to activate complement, but the usage of patient sera exhibit some drawbacks such as effects of serum components other than anti‐RhoGDI2 antibodies on complement activation.…”
Section: Discussionmentioning
confidence: 79%
“…1) Human microvascular endothelial cells (HMECs; catalogue no. CRL-3243; purchased from ATCC ® , Manassas, VA, USA) were cultured in MCDB131 basic media for HMECs (Invitrogen and Gibco, Waltham, MA, USA) supplemented with 5% FCS, 10 mM L-glutamine, 10 ng/ml recombinant human EGF, 10nM hydrocortisone, and 1% penicillin/streptomycin (100 U/ml and 100 ug/ml, respectively) ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…No. : 30-2003 from ATCC ® ) supplemented with 10% FCS, 2mM GlutaMax (Gibco), 1mM sodium pyruvate, 10mM HEPES, and 100 U/ml penicillin/100 ug/ml streptomycin ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Protein-DNA complexes were analyzed by electrophoresis in 6% non-denaturing polyacrylamide gels and visualized with LightShift Chemiluminescent EMSA Kit (Thermo). The activity of NFkB and NFAT signaling was analyzed with EMSA and luciferase assays, respectively, as described previously ( 50 , 51 ).…”
Section: Methodsmentioning
confidence: 99%
“…(A, B) Effect of KTx-IgG on TNF-α protein release from HMECs (A) Upon a 24-hour incubation with 1.0 mg/ml Con-IgG or KTx-IgG from patients with or without vasculopathy or baseline control (pg/ml, n=3 each) and (B) Upon a 24-hour stimulation with 1 mg/ml KTx-IgG from patients with vasculopathy (n=5 each) in the presence or absence of the following stimuli: a) mitogen phorbol-myristate-acetate (PMA, concentration 50 ng/ml), b) thrombin (0.1 U/ml), and c) PAR-1 inhibitor (BMS200261, 1 µM); and (C, D) Analysis of NFkB and NFAT activation in response to KTx-IgG from patients with vasculopathy compared to Con-IgG (each 1 mg/ml for 24 hours). The activity of NFkB and NFAT signaling was analyzed with EMSA and luciferase assays, respectively, as described previously ( 50 , 51 ). The data were analyzed with repeated ANOVA and expressed as Mean +/- SD with *P<0.05, **P<0.01, and ***P<0.001.…”
Section: Supplementary Materialsmentioning
confidence: 99%